Legal Protection Against Illegal Orangutan Trade - Salsabila, Aina Nashira (Library of Sultan Agung Islamic University, 2023)
The archipelago is vast, even become the largest archipelagic country in the world. Having many islands makes Indonesia rich in diversity of flora and fauna, one of which is the orangutan wildlife that lives in the forests of Indonesia. Illegal trade in protected wildlife is still rampant due to the lack of public awareness about the importance of preserving nature so that the population of protected wildlife does not experience extinction. The trade-in wildlife does not only cover the national level, it has even penetrated at the international level. One of the regulations regarding the protection of the international wildlife trade is the Convention on International Trade of Endangered Species of Wild Fauna and Flora (CITES). Legislation regarding the trade-in protected wildlife in Indonesia has been regulated in Law Number 5 of 1990 concerning the Conservation of Biological Resources and Their Ecosystems. The writing of this paper uses data collection methods from various sources such as articles, journals, and some websites on the internet. The novelty of this research is to discuss the legal protection of the orangutan wildlife trade in Indonesia. Ineffective government regulations make there still a lot of illegal wildlife trade.